(untitled) (Research, Society and Development, 2024)
This article aims to demonstrate the importance of climate change mitigation to reduce the frequency and intensity of extreme events, thereby protecting the right to life and human dignity. The methodology used was bibliographic research, based on books, scientific articles, legal theses, and other reliable sources to build a robust and interdisciplinary theoretical foundation. The results highlight the interconnection between climate change and extreme events, showing how these phenomena directly impact human life, causing significant material and socioeconomic damages. Examples of extreme events in Minas Gerais illustrate the vulnerability of communities and the urgent need for effective mitigation and adaptation strategies. The conclusion reinforces that protecting the right to life, guaranteed by the Federal Constitution and international treaties, depends on coordinated actions between governments, civil society, and the private sector. Rigorous implementation of public policies, such as the Paris Agreement, and the promotion of sustainable practices are essential to facing one of the greatest challenges of the 21st century. This study reaffirms the importance of an integrated and collaborative approach, based on scientific evidence and respect for human rights, to ensure a sustainable and secure future for all.